Live witnesses in Chinese criminal courts: obstacles and reforms - Guo, Zhiyuan (International journal of law, crime and justice, 2020)
China has adopted a series of reforms to encourage witnesses to testify in court in amending its Criminal Procedure Law (CPL) in 2012. However, empirical surveys have revealed that these and subsequent reforms have failed to enhance the rate of witness appearances in criminal trials. This article provides an overview of the history of Chinese criminal procedure law addressing live witness issues in Part I. Part II analyzes the reasons that the reforms have been unsuccessful, suggesting that they were overly focused on witness's motivations and missed institutional resistance to live testimony. Since police officers were not required by law to testify in court until 2010, and police are considered a special subgroup of witness in China, police witnesses are examined separately in Part III. In Part IV, recommendations for further reform are put forward to remedy past failures.